Effect of Scapular Proprioceptive Neuromuscular Facilitation Versus Scapular Mobilization on Pain and Function in Adhesive Capsulitis – A Pragmatic Randomized Clinical Trial - Bhavika, P. Gohel; R., Kamalakannan; Vinosh Kumar, Purushothaman (INTI International University, 2023)
Objectives: The aim of this study was to compare the effects of scapular proprioceptive neuromuscular inhibition technique and scapular mobilisation on pain, range of motion and function in participants with adhesive capsulitis. Methods: 30 participants were randomly allocated into two groups: Group A – Scapular PNF+ conventional physiotherapy, Group B - Scapular Mobilization + Conventional physiotherapy. The intervention was applied for 6 days/ week for 2 weeks. The Numerical Pain Rating Scale, Shoulder range of motion and Shoulder pain and disability index was taken before and after the intervention in both groups. Results: Non-parametric tests were used to analyse the data. Within the group data was analysed with Wilcoxon signed rank test. Between the group data was analysed with Mann Whitney U test. Result was found to be significant, p value 0.001 for within group. Between group analysis showed p value <0.05, suggesting significant difference between the effect of two interventions. Conclusion: Scapular mobilisation along with conventional physiotherapy was found to be more effective in reducing pain, improving range of motion and function in participants with Adhesive Capsulitis